2009
DOI: 10.1103/physreve.80.036314
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport measurements in turbulent rotating Rayleigh-Bénard convection

Abstract: We present experimental heat transport measurements of turbulent Rayleigh-Bénard convection with rotation about a vertical axis. The fluid, water with a Prandtl number (sigma) of about 6, was confined in a cell with a square cross section of 7.3 x 7.3 cm2 and a height of 9.4 cm. Heat transport was measured for Rayleigh numbers 2 x 10(5) Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…The agreement between heat transfer measurements in nonrotating liquid metal and the inertial scaling [4], shown in Fig. 2B, suggests that the transition between rotationally constrained and weakly rotating convection should occur when Ro c ≈ 1 ( [7]).…”
Section: Methodsmentioning
confidence: 50%
See 2 more Smart Citations
“…The agreement between heat transfer measurements in nonrotating liquid metal and the inertial scaling [4], shown in Fig. 2B, suggests that the transition between rotationally constrained and weakly rotating convection should occur when Ro c ≈ 1 ( [7]).…”
Section: Methodsmentioning
confidence: 50%
“…The dashed line in Fig. 2B shows the inertial scaling law [4] for the median experimental value of Pr = 0:025. Experimental heat transfer data trend with this scaling law, but are 7% less than predicted on average.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental [7]- [13] and numerical studies [11]- [16] at constant Ra and Pr have shown that at moderate rotation rates the convective heat transfer is higher than for the nonrotating case. This heat transport enhancement with respect to the non-rotating case has been ascribed to Ekman pumping [8], [10]- [13], [15]- [18].…”
mentioning
confidence: 99%
“…This process depends strongly on Ra and Pr [11] and the boundary conditions [19]. Liu and Ecke [7] showed that this increase in Nu can be presented in several ways, as the rotation rate can be expressed by the Taylor Ta number, which measures the effect of the rotational Coriolis force, and the Rossby Ro number, which indicates the relation between the buoyancy and Coriolis forces. Here we choose the latter since Ro indicates when Ekman pumping effects become important with respect to buoyancy effects [12].…”
mentioning
confidence: 99%